Defence compounds and their taxonomic significance in Euphorbiaceae - Hemalatha, A.; Radhakrishnaiah , M. (Rheedea, 1993)
The products of shikimate (proanthocyanidins, tannins, caffeic acid, chloro genic acid, alkaloids) and acetate mevalonate (steroids, terpenoids, iridoids) pathways in 86 members of Euphorbiaceae are analysed and interpreted in terms of their advancement. The incidence of caffeic acid or its isomer in a number of taxa of the present study adduces its efficacy, The evolutionary strategies among some of the ecotypes/cultivars are discussed in the light of biosynthetic pathways.